The Influence of Work Culture and Organizational Commitment on Employee Loyalty at PT. Nawa Setia Perkasa - Winda Dwi Agustini; Asep Jamaludin; Nandang (PT. Berkah Digital Teknologi, 2025)
Purpose of the study — This research aims to determine the partial or simultaneous influence between work culture and organizational commitment on employee loyalty at PT. Nawa Setia Perkasa. Research method— This type of research uses descriptive verification with a quantitative approach and is carried out using a questionnaire method. The sample for this research was 141 respondents using the Slovin formula. The analytical model used in this research is a multiple linear regression analysis model. Result— The results show that there is a partial influence of work culture on employee loyalty, a partial influence of organizational commitment on employee loyalty, and a simultaneous influence of work culture and organizational commitment on employee loyalty. Conclusion— High work culture and organizational commitment have a positive effect on employee loyalty at PT Nawa Setia Perkasa, creating a supportive work environment and increasing employee loyalty. Weak work culture and organizational commitment can reduce employee loyalty due to a lack of strong organizational commitment and emotional investment from the company.